Tenure Rights and Beyond: Community Access to Forest Resources in Latin America - Larson, A.M.; Cronkleton, P.; Barry, D.M.; Pacheco, P. (Center for International Forestry Research, 2008)
This occasional paper is the result of research carried out from 2006 to 2008 on the effects of new tenure rights for forest-based communities in Latin America on access to forest resources and benefits. Focused on seven different regions in four countries, the paper examines changes in statutory rights, the implementation of those rights in practice, and the extent to which they have led to tangible new benefits from forests, particularly to new sources of income. The research sites included several types of conservation and settlement communities in the Brazilian Amazon, an indigenous territory and agro-extractive communities in Bolivia, indigenous territories in Nicaragua and community forest concessions and highland communal forests in Guatemala. Though the granting of tenure rights signifies an important achievement for many communities, new statutory rights do not automatically turn into rights in practice. Virtually all of the cases — even those in which benefits have been significant — encountered substantial challenges along the road from rights to benefits: conflicts with other resource claimants; the failure of the state to define the tenure right appropriately or defend it effectively; problems with local authorities and governance institutions; the superposition of new models over existing institutions; obstacles to community engagement with markets; and the lack of systems to support forest resource management. The bundle of rights granted is sometimes overwhelmed by an accompanying bundle of responsibilities, or limited by restrictions on use, and may include an important ongoing decision-making role for certain state authorities. Institutional arrangements are also shaped by a variety of local authorities, some of which have been created or given substantial new powers in the reform process but lack experience and clear accountability relations. The state often appears more concerned with establishing management regulations than with defending community rights; for their part, communities and their organizations are forced to waste time and resources defending their rights from outside interests, rather than using these to strengthen local governance and forest management capacity. Policy frameworks have generally failed to establish an enabling environment for endogenous, community-based management opportunities. The gains that have been won and the potential of these processes for improving rights and livelihoods demonstrate the value of promoting efforts to overcome these obstacles.